2000
DOI: 10.1291/hypres.23.supplement_s1
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Digitalislike Factor: An Update

Abstract: bain is the most promising candidate for a circulating hormone to regulate a number of physiological functions, including hypertension, and that other minor substances may also exist as endogenous digitalislike factors. Most of the symposium contributors submitted papers to this journal. I am going to summarize briefly the research history and current research results on endogenous digitalislike factors (EDLF).(Hypertens Res 2000; 23 Suppl: S1-S5)Key Words: endogenous digitalis, ouabain, digoxin, central nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It is also locally produced in other tissues, such as the hypothalamus (16,18). Its physiological role has not been clarified (37). It has been suggested that ouabain may act as a natriuretic hormone (22,38), but unlike most other natriuretic factors, it may also have a vasoconstrictive effect (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is also locally produced in other tissues, such as the hypothalamus (16,18). Its physiological role has not been clarified (37). It has been suggested that ouabain may act as a natriuretic hormone (22,38), but unlike most other natriuretic factors, it may also have a vasoconstrictive effect (39).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of cardiotonic steroids are also high in several kinds of salt-dependent hypertensive animals (16, 24, 25). Indeed, PST2238, a ouabain antagonist, lowers blood pressure in salt-dependent hypertensive rats and in certain patients with essential hypertension (17,18,91). Thus these cardiotonic steroids may be involved in the etiology of salt-dependent hypertension.…”
Section: Early Studies On the Role Of Endogenous Cardiotonic Steroidsmentioning
confidence: 99%
“…PST2238 lowers the arterial blood pressure in ouabain-induced hypertensive rats (18) and Milan hypertensive rats (17), in which endogenous ouabain is increased. Recent phase II clinical studies in Europe show that PST2238 effectively lowers blood pressure in essential hypertensive patients (91). On the other hand, thiazide diuretics have been widely used as antihypertensive drugs for a long time.…”
Section: Therapeutic Potential Of Na ؉ /Ca 2؉ Exchange Inhibitors In mentioning
confidence: 99%
“…The structural similarity between the different CS-like compounds identified so far suggests a common precursor and biosynthetic pathway. Numerous studies have shown that the endogenous CS-like compounds are synthesized in and secreted by the adrenal gland (Takahashi, 2000;Schoner, 2002). The level of these endogenous CS-like compounds in human plasma varies between 0.1 and 1 nM (Hamlyn et al, 1996;Goto and Yamada, 1998) and their physiological role, despite extensive research, remains obscure.…”
Section: Namentioning
confidence: 99%